Roles of Cave Maps as Geoinformation in Supporting Geotourism: Practice in Gunung Sewu Unesco Global Geopark - Ristiawan, Angga Wahyu (Departemen Teknik Geologi, 2019)
Cave map is a projection of a cavity or speleological phenomena in a certain media. It is categorized as one of the geoinformation because it represents and is related with caves as the geological features. Projection of caves has a considerably important role in comprehending several characteristics of the caves themselves. Through the visualization and modeling, scientists are able to reconstruct the process of speleogenesis, ecology of the cave, or hydrological aspects in order to develop a firm management strategy e.g. engineering, conservation, or the emerging tourism. This paper aims to describe how cave maps hold crucial roles in providing geoinformation which can be used to explain various features and information on scientific and tourism activity aspects. Using qualitative method, it uses perspective from tourist and study of cave cartography to enact the understanding of cave maps and its roles in geoinformation, geotourism, and geoconservation. Cave tourism as the part of the geotourism, currently is having significant role in increasing income, strengthening people’s economy, and raising awareness to the tourist about how a geological process craving and shaping such as aesthetically and breath-taking features like the ornament and cave’s passage. Aside from the scientific information, cave maps are openly used to show about the risk and danger inside the cave and how to mitigate the hazard. Furthermore, it also has role to develop a zoning to regulate the tourist behavior and attraction inside the cave which is crucial to preserve and maintain the cave.